Mutations Affecting the Ability of the Escherichia coli UmuD′ Protein To Participate in SOS Mutagenesis - Ohta, Toshihiro (American Society for Microbiology, 1999)
The products of the SOS-regulated umuDC operon are required for most UV and chemical mutagenesis in Escherichia coli, a process that results from a translesion synthesis mechanism. The UmuD protein is activated for its role in mutagenesis by a RecA-facilitated autodigestion that removes the N-terminal 24 amino acids. A previous genetic screen for nonmutable umuD mutants had resulted in the isolation of a set of missense mutants that produced UmuD proteins that were deficient in RecA-mediated cleavage (J. R. Battista, T. Ohta, T. Nohmi, W. Sun, and G. C. Walker, Proc. Natl. Acad. Sci. USA 87:7190–7194, 1990). To identify elements of the UmuD′ protein necessary for its role in translesion synthesis, we began with umuD′, a modified form of the umuD gene that directly encodes the UmuD′ protein, and obtained missense umuD′ mutants deficient in UV and methyl methanesulfonate mutagenesis. The D39G, L40R, and T51I mutations affect residues located at the UmuD′(2) homodimer interface and interfere with homodimer formation in vivo. The D75A mutation affects a highly conserved residue located at one end of the central strand in a three-stranded β-sheet and appears to interfere with UmuD′(2) homodimer formation indirectly by affecting the structure of the UmuD′ monomer. When expressed from a multicopy plasmid, the L40R umuD′ mutant gene exhibited a dominant negative effect on a chromosomal umuD(+) gene with respect to UV mutagenesis, suggesting that the mutation has an effect on UmuD′ function that goes beyond its impairment of homodimer formation. The G129D mutation affects a highly conserved residue that lies at the end of the long C-terminal β-strand and results in a mutant UmuD′ protein that exhibits a strongly dominant negative effect on UV mutagenesis in a umuD(+) strain. The A30V and E35K mutations alter residues in the N-terminal arms of the UmuD′(2) homodimer, which are mobile in solution.